Incidence of Fever in Labor and Risk of Neonatal Sepsis. Issue 4 (December 2017) - Towers, C.V.; Yates, A.; Zite, N.; Smith, C.; Chernicky, L.; Howard, B.
Abstract : ( Am J Obstet Gynecol . 2017;216(6):596.e1–596.e5) Maternal fever alone during labor may be a sign of chorioamnionitis and an indication for antibiotic therapy. However, there are no published obstetrical guidelines devoted to the management of chorioamnionitis. Reports of physician diagnosed chorioamnionitis may underestimate rates (3.1% whereas a few large studies suggest it to be closer to 7%), and clinical management varies across institutions. Therefore, in the present study, authors evaluated the rate of fever during labor and assessed risk for early-onset neonatal sepsis in newborns delivered from mothers with intrapartum fever compared with those delivered from mothers without fever.